Strongly regular m-Cayley circulant graphs and digraphs - Martínez, Luis (Ars mathematica contemporanea, 2015)
The first part of this paper is a survey about strongly regular graphs and digraphs admitting a semiregular cyclic group of automorphisms. In the second part, some new types of such digraphs, called uniform and almost uniform, are studied. By using partial sum families, the form of the parameters is determined and some directed strongly regular graphs derived from these partial sum families with previously unknown parameters are obtained.
Keywords: almost-uniform partial sum families; krepko regularni grafi; krepko regularni usmerjeni grafi; m-Cayley circulant; m-Cayleyjev cirkulant; skoraj-uniformne družine delnih vsot; strongly regular digraphs; strongly regular graphs; uniform partial sum families; uniformne družine delnih vsot